A simple method to evaluate the effectiveness of encapsulation materials for perovskite solar cells. (1st December 2016) - Wilderspin, Timothy J.; De Rossi, Francesca; Watson, Trystan M.
Highlights: A method for screening encapsulant materials for perovskite solar cells is presented. RGB (red, green, blue) colour analysis can track perovskite degradation to PbI2 . Detailed UV-Vis and XRD analysis supports the more rapid RGB data. Abstract: Solution processed perovskite solar cells are an exciting development in the field of photovoltaics achieving power conversion efficiencies of over 20%. Nevertheless, stability issues are still limiting the successful entry of this technology into the PV market. Rapid degradation has been observed and reported as the result of different factors, such as light, humidity and temperature, simultaneously present during real operation. It is felt within the PV community that proper, effective encapsulation is one of the key contributors to increasing perovskite lifetimes. This work presents a simple and effective method based on RGB (red, green, blue) colour measurements to track perovskite degradation to lead iodide (PbI2 ) using time lapse photography and thus evaluate the effectiveness/reliability of different encapsulation methods and materials. This technique gives a clear indication of when the perovskite has fully degraded and the impact of different encapsulants on degradation rate. This is supported by other analytical techniques, such as UV-Vis spectroscopy and XRD.